Effect of shot peening on surface mechanical properties of selective laser melting TC4 titanium alloy - LIU Yiran; LI Lei (Fenmo yejin jishu, 2025)
Selective laser melting TC4 titanium alloy samples were shot peening with ϕ2.3 mm and ϕ4.0 mm ceramic shots respectively. The surface morphology, surface roughness, surface friction coefficient, surface wear morphology and surface microhardness of the samples were observed and analyzed by laser confocal microscope, comprehensive surface property tester, scanning electron microscope and Vickers microhardness tester. The results show that after shot peening, the surface roughness of the samples decreases by 80.2%～86.3%. For the samples treated with ϕ2.3 mm shot, the surface roughness increases gradually with the increase of shot peening time. The surface roughness of the samples treated with ϕ4.0 mm shot decreases with the increase of shot peening time. The shot peening diameter, shot peening time and load all have effects on the friction coefficient of the sample. When the load is 10 N, the friction coefficient of the sample treated with ϕ2.3 mm shot changes obviously, while the friction coefficient of the sample treated with ϕ4.0mm shot changes little. When the load increases to 20 N, the average friction coefficient of the samples treated with ϕ2.3 mm shot slows down, while the friction coefficient of the samples treated with ϕ4.0 mm shot has little change. The surface of selected laser melted TC4 alloy after shot peening has obvious wear marks and plastic deformation, and the wear mechanism is mainly abrasive wear. The friction and wear properties of the surface of the material are improved by the reasonable matching of the diameter of the shot and the strengthening time of the shot peening, and the deformation of the material is effectively inhibited during the friction process.